EFFEKTIVITAS PEMANFAATAN MEDIA BLOG MENINGKATKAN KEMAMPUAN SISWA DALAM PEMBELAJARAN MENULIS CERPEN DI KELAS XI SMA NEGERI 2 LAWE BULAN - Dwi Azura; James Marudut; Rekaza Akbar (STKIP USMAN SAFRI KUTACANE, 2022)
This study aims to determine the improvement of short story writing skills through the use of blog media in class XI students of SMA Negeri 2 Lawe Bulan in the 2021/2022 academic year. The population in this study were all students of class XI and a sample of 36 people. The method used in this study is an experimental method with a one group pretest and posttest design with data analysis using the